A comparative analysis of startups financing in Vietnam - Nguyen, Thi Hanh (Journal of International Economics and Management, 2022)
The purpose of this paper is to compare the potential and funding amount of startups financing in Vietnam during the period of 2010 – 2018. Probit regression is employed to clarify the differences in fundraising potential among some industries. In addition, linear regression is applied to investigate the capacity of startups financing. The finding shows that startups in financial technology (fintech) and e-commerce have advantages in raising capital. Furthermore, startups in service technology dominate the capacity of raising money. In addition, the study shows that the older of startups age, the higher potential and capacity of outside financing. The study attributes valuable results to both academic and practical fields. Entrepreneurs can, thus, seize opportunities successfully in new ventures.